Is There a Place for Libraries of Things in Irish Public Libraries? - Hunter, Alison (My University, 2024)
The aim of this research study is to understand whether there is “a place for Libraries of Things in Irish public libraries”; to investigate the strategy, barriers and drivers involved in implementation of Libraries of Things (LoTs) in Ireland, and to consider whether a model for offering LoTs might be adapted to the current situation in Irish public libraries, based upon the research findings. Qualitative data for the study was gathered by interviews with 7 senior public librarians in Ireland, and a comparative interview with an American librarian. Findings suggest that there is wary support for LoTs, amongst Irish public librarians. The main concerns identified were risk, staffing, funding and space/storage. Many Irish libraries currently offer “Things”. The research shows that there is already a place for Libraries of Things in Irish public libraries, but that this is currently dependent on individual local authorities, and not an explicit national strategy.
HECA (Higher Education Colleges Association) Research Conference 2024
Shared with the kind permission of the HECA Research Working Group.
Keywords: Library of Things; Circular Economy; Public Library; Ireland; Sharing Economy; Sustainability; Libraries—Special collections—Nonbook materials; Public Libraries; Libraries and Community; Circular Economy; Inclusive Society; Making Ireland; Smart & Sustainable Planet; LIBRARY; Library of Things; Public libraries; Sharing Economy; Tool Library; circular economy